Pengaruh beras terhadap budaya pemanfaatan sagu di Maluku - Naldi, Ari; Chastine, Belathea (Institute for Advanced Science, Social, and Sustainable Future, 2024)
People in the eastern part of Indonesia - Papua, West Papua, North Maluku, and Maluku, are the majority of the Indonesian population who utilize sago trees as a source of food and for other needs. Unfortunately, the culture of sago utilization in these areas, especially Maluku, has begun to degrade along with cultural changes over time since the Transmigration and Green Revolution programs were implemented by the Central and Local Governments. In this research, there are problems that need to be analyzed related to the main factors of the cultural evolution of staple food consumption, from sago to rice, so that it can threaten the sustainability of sago plants in Maluku Province. This research uses a literature review approach by utilizing journal articles, reports of government and non-government institutions, and other textual documents to be processed using the content analysis method. The data that has been selected is contextualized into the research article and linked to the theory of cultural evolution to discuss the cultural changes occurring in Maluku in relation to political, population and environmental pressures. In this research, it is found that political policies, Transmigration and Green Revolution, can be said to be the main factors of the cultural degradation of sago utilization in Maluku in many aspects, both for food consumption and for other needs.